Guidelines for diagnosis, prevention, and treatment of hand eczema. (3rd March 2022) - Thyssen, Jacob P.; Schuttelaar, Marie L. A.; Alfonso, Jose H.; Andersen, Klaus E.; Angelova‐Fischer, Irena; Arents, Bernd W. M.; Bauer, Andrea; Brans, Richard; Cannavo, Alicia; Christoffers, Wianda A.; Crépy, Marie‐Noelle; Elsner, Peter; et al.
Abstract: Background: Hand eczema is a common inflammatory skin disorder. Health care providers need continuously updated information about the management of hand eczema to ensure best treatment for their patients. Objectives: To update the European Society of Contact Dermatitis guideline on the diagnosis, prevention, and treatment on of hand eczema. Method: The Guideline Development Group (GDG) was established on behalf of the ESCD. A call for interest was launched via the ESCD website and via the ESCD members' mailing list. Appraisal of the evidence for therapeutic and preventive interventions was applied and a structured method of developing consensus was used and moderated by an external methodologist. The final guideline was approved by the ESCD executive committee and was in external review on the ESCD webpage for 1 month. Results: Consensus was achieved for several statements and management strategies. Conclusion: The updated guideline should improve management of hand eczema.